Madeirasquilla tuerkayi, a new genus and species of mantis shrimps from Madeira Island, eastern Atlantic (Crustacea: Stomatopoda: Nannosquillidae) - Ďuriš, Zdeněk (Zootaxa, 2018)
Madeirasquilla tuerkayi is described as a new genus and species of the nannosquillid mantis shrimps (Stomatopoda) based on a single specimen collected from Madeira, eastern Atlantic. That specimen is remarkable by a combination of the following morphological characters: rostral plate with three sharp anterior projections; antennal protopod with two mesial and one ventral papillae; cornea subglobular; raptorial claw dactylus with 11 or 12 teeth, and with acute proximal tooth on outer margin; pleonite 6 with strong posterolateral spine and two posteriorly directed sternal spines; telson bearing smooth shield-like dorsal prominence with acute median spine posteriorly; four pairs of fixed primary teeth posteriorly on the telson; outer primary spine of uropodal protopod longer than inner primary spine. The separate position of the new genus is supported also by molecular comparison. A key to the genera of the family Nannosquillidae is proposed.